Caracterización de experiencias de aprendizaje personalizado en el ámbito de las relaciones lógico matemáticas en los niños y niñas de 4 a 5 años - Bonilla Suntasig, Aida Clemencia (2017)
Logical mathematical relationships are important along to the children life, in the pre-school stage the children understand, assimilate, know, and experice. This will be possible only if the teacher construct and give an adequate educational environment for the child interact with objects, explore them, investigate them, discover and make their own learning. The present investigation had as objective to determine the process of the characterization of the personalized learning in the logical mathematical relations in the children from 4 to 5 years and thus a diagnosis was obtained in which parents, teachers and children participated. The methodology used was qualitative and quantitative, the modality of the research was field investigation, and bibliographic data such as the survey, interview and the observation sheet, the same ones that were applied in The level 2 of Initial Education of the institution, for which it was considered contents referring to logical mathematical relationships and personalized learning through the search of information already consulted in books, magazines, documents and the web, which was oriented to know the most common problems of children in logical mathematical relations, finding the following difficulties as lack of motivation before the class hour, lack of physical space for the adequacy of learning environments, but above all The nursery teachers of the Educational Institution still apply a traditionalist learning,...